Characterization of Respiratory Tract Bacterial Flora Post-Tracheostomy in Intensive Care Unit Patients - Dukare, Prashant Manohar (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: Tracheostomy is frequently performed in intensive care unit (ICU) patients to facilitate ventilation and improve airway management. This procedure alters the normal bacterial flora of the respiratory tract, potentially leading to infections. Aim: To characterize the bacterial flora present in the respiratory tract of ICU patients following tracheostomy. Methods: A total of 100 ICU patients who underwent tracheostomy were included. Respiratory samples were collected for microbiological analysis. Inclusion criteria included adult patients with a tracheostomy for at least 48 hours; exclusion criteria included patients with recent antibiotic therapy. Results: The study identified a diverse range of bacterial species, with the most prevalent being Pseudomonas aeruginosa and Staphylococcus aureus. Conclusion: The findings highlight the need for continuous monitoring of bacterial flora in tracheostomized patients to inform antibiotic therapy and infection control practices. Keywords: Tracheostomy, Respiratory tract, Bacterial flora, Intensive care unit, Infections.